Organizational and economic mechanism of infrastructure development in the field of customs services: regional aspect - A. A. Lisitsa (Вестник университета)
The article analyzes the organizational and economic mechanism of customs services infrastructure development on the example of the Far Eastern Federal District.   The purpose of the study is to assess spatial and territorial location of customs and near-customs infrastructure elements, as well as features of economic activity of infrastructure subjects such as customs authorities, customs representatives, customs carriers, duty-free stores owners, temporary storage warehouses owners, customs warehouses, free warehouses, andauthorized economic operators.   The relevance of the conducted scientific research is conditioned by the need to apply a comprehensive approach to assessment of the Far East region infrastructure from the position of providing customs services throughout the foreign economic activity supply chain.   The task of the study is to determine the potential of the Far Eastern Federal District infrastructure in the context of changing parameters of demand from the participants of foreign economic activity.   The research concept is based on the service-oriented customs administration theory and general methodological approaches to regional economic research. The results obtained allow us to conclude that the demand for customs services exceeds the available supply of regional infrastructure. The problems of the regional mechanism functioning have been outlined: carrying and storage capacities deficit, low level of established checkpoints infrastructure involvement, their insufficient equipment, area and throughput capacity, as well as shortcomings in technological processes organization, including when making decisions on the spatial location of customs infrastructure facilities, investment resources allocation, and the lack of interconnected regulation.